THE BOTANIC GARDEN IN PRUHONICE AND ITS IRIS COLLECTION - BLAZEC, M. (Annali di Botanica, 2000)
The Botanic Garden of the Academy of Sciences, the highest sc ientific body in Czechoslovakia, was established in January 1963. The goals of the Garden were very ambitious: it was planned as the future main Botanic Garden of the state. Therefore the collections were to be extensive, up-to-date and useful for scientific purposes. The site of the Botanic Garden was the famous park of Pruhonice, covering 250 hectares, and for new specialised collections a garden of 20 hectares was also available nearby.